Dynamic Assessment of Allergen-Specific Immunotherapy in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Allergic rhinitis (AR) is a common chronic disease caused by immunoglobulin E (IgE)- mediated inflammatory response in the nasal mucosa.1 It not only adversely affects study and work performance but imposes considerable economic and health burdens on society. AR is estimated to affect 10%–30% of adults and 40% of children and its prevalence is still on the rise globally, particularly in developing countries. Such an increase is also observed in China, the largest developing country in the world with a population of 1.4 billion. Therefore, comprehensive and continuous monitoring is urgently needed to develop health policies aiming at reducing the burden of AR. While numerous studies have studied the epidemic of AR in children, 5–7 relatively fewer are available in adults among whom AR prevalence and relevant risk factors may be distinct from children in China [19,20]. Existing results of AR prevalence in adults showed large variation. For example, Li et al reported 6.1% of adult participants in Guangzhou having AR, which was much lower than the prevalence in Beijing (13.5%) and Baoding (19.1%). Moreover, these 2 studies found opposite findings in terms of differences between urban and rural areas. Both discrepancies suggest that estimates based on samples restricted to certain regions may depend on local characteristics and cannot fully reflect the overall picture of China. To address this gap, population-based nationwide studies had been performed in 11 and 18 large cities and demonstrated that the AR prevalence was 11.1% and 17.6%, respectively, in 2005 and 2011. However, these data neither were collected in recent years nor could be generalized to rural areas. In addition, although possible risk factors have been identified in previous studies, their impacts at extreme ends of distribution on AR are rarely assessed earlier mainly due to limited statistical power. Besides, no study has explored potential interactions between risk factors and sex, residence, and geographic region, which can facilitate more customized intervention measures [20].This article shows the effectiveness of antigen-specific immunotherapy in 79 sick children with suspected allergic rhinitis. In order to study the course of allergic rhinitis, the effectiveness of the diagnostic and treatment the method was assessed using an individual questionnaire offered by Allergic Rhinitis and its Impact on Asthma (ARIA).